Bacteriological Study on Surgical Site Infection in Rangpur Medical College and Hospital - Islam, Md Hamidul; Mishu, Minim Parvin; Afroze, Nusrat; Mahmud, MH; Islam, Md Shariful; Shah, Md Shahin (Journal of Rangpur Medical College, 2022)
Background: Surgical site infections (SSIs) is a major problem in both developed and developing countries. In developing countries like Bangladesh, infection in surgical patients has been appearing as a serious risk due to insurgence of drug resistance. Surgical site infections (SSIs) contribute significantly to increased health care costs in terms of prolonged hospital stay and lost working days. The problem was largely unexplored in Rangpur Medical College and Hospital, Rangpur. Objective: The aim of the study was to evaluate the bacteriological study on surgical site infections in Rangpur Medical College & Hospital. Methods: This cross-sectional observational study was conducted in the Department of Surgery at Rangpur Medical College Hospital. 72 patients of all ages, sex who developed surgical site infection were included through purposive sampling for observation and clinical follow up and wound swab was microbiologically evaluated. Results: Of the 72 cases, SSI developed 30.6% (22) following elective surgery and 69.4% (50) following emergency surgery. 7 cases were associated with co-morbid conditions like diabetes mellitus (2), malignancy (4) and tuberculosis (1). Most common organisms were Escherichia coli (30 /54) followed by Staphylococcous aureus (14/54), Pseudomonas (07/54) and Klebsiella (03/54).The antibiogram pattern of the organism isolated from wound swab of SSIs were analyzed with commonly used antibiotics. Resistance of Escherichia coli to Amoxycillin, Cotrimoxazole, Doxycycline and Nalidixic acid were 100%, 91.5%, 71.4% and 60.5% respectively. In case of, Staphylococcus aureus 87.5% were resistant to penicillin and Cotrimoxazole. Resistance of Pseudomonas spp. to Ciprofloxacin, Ceftazidime and Gentamicin were 31.2%. 6.3% and 50% respectively. In case of Klebsiella spp, it showed that 100% strains were resistant to Amoxycillin like Esch. coli but all strains were sensitive to both Ceftriaxon and Imipenem. Conclusion: The study emphasizes the need for the evidence-based infection control and antibiotic prescription policies in the hospital. J Rang Med Col. September 2022; Vol. 7, No. 2:12-19